Mode Berpakaian Penduduk Simalungun Awal Abad Abad Ke-20: Analisis Narasi Foto - Nababan, Celynta Salonica; Manihuruk, Leony Octora; Simbolon, Sixtus; Rambe, Tappil (Universitas Syiah Kuala, 2025)
The evolution of clothing in contemporary times is deeply intertwined with the practices established during the Dutch colonial era.This study focuses on the traditional attire of the Simalungun community in the early 20th century, exploring how their clothing transformed as a result of acculturation from both Arab and Dutch influences. To conduct this research, we employed the Historical Methodology framework outlined by Kuntowijoyo, which involves five key stages: Topic Selection, Heuristics, Interpretation, Verification, and Historiography.Our investigation highlights clothing as a vital aspect of the Simalungun community's identity, demonstrating that their current attire reflects a blend of European, Arabic, and Simalungun styles. By examining archival sources and contemporary traditional clothing, we emphasize the importance of preserving these garments against the backdrop of modernity.This research not only aids writers, readers, and scholars but also serves as a foundation for future studies focused on the role of clothing in Indonesia's cultural landscape.